Cross-border acquisitions from developing countries under decreasing returns to scale - Dong, Quan (2021)
We assume that a firm from a developing country wants to acquire a firm from a developed country with better technology. The acquirer, which may be a private firm or a state-owned firm, seeks to improve its efficiency in production. We assume that at most there is one acquisition, and that it needs to be authorized by both the government of the developing country and that of the developed country. Firms face decreasing returns to scale. We find that if the level of inefficiency of the acquirer is very high, the government of the developed country forbids acquisitions. The private firm from the developing country is the acquirer in two cases: if the level of inefficiency of the firms from that country is low and if it is high. If the level of inefficiency is intermediate, the acquirer is the state-owned firm.